PENGARUH WORK-LIFE BALANCE TERHARAP WORK ENGAGEMENT PADA GIG WORKERS DENGAN WORK MEANINGFULNESS SEBAGAI VARIABEL INTERVENING (STUDI PADA MITRA PENGEMUDI STARTUP BISNIS TRANSPORTASI ONLINE) - Febriani Harianto; Nuri Herachwati (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract Aiming to determine the effect of work-life balance on work engagement through work meaningfulness as mediation for gig workers, this research is specifically for online motorcycle drivers in Indonesia, especially in Surabaya and its surroundings. The object of the research was related to the phenomenon of online motorcycle driver profession in Indonesia, which amounted to 2.7 million, due to the flexibility offered and proven to reduce TPT (Integrated Unemployment Rate). Research was conducted with quantitative methods by collecting survey data using questionnaires to 491 online motorcycle drivers. Data is processed using structural equation modeling with AMOS software. The result show that work-life balance influences work meaningfulness and work engagement, work meaningfulness influences work engagement, and work meaningfulness can mediate the influence between work-life balance on work engagement. This study is expected to enrich the research literacy of the gig workers object, especially online motorcycle drivers, due the gig workers are not permanent employees of a company. Keywords : Work-Life Balance, Work Meaningfulness, Work Engagement, Gig Workers, Gig Economy, Motorcycle Drivers, Startup